2007
DOI: 10.1016/j.socnet.2006.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in exponential random graph (p*) models for social networks

Abstract: This article reviews new specifications for exponential random graph models proposed by Snijders et al. [Snijders, T.A.B., Pattison, P., Robins, G.L., Handcock, M., 2006. New specifications for exponential random graph models. Sociological Methodology] and demonstrates their improvement over homogeneous Markov random graph models in fitting empirical network data. Not only do the new specifications show improvements in goodness of fit for various data sets, but they also help to avoid the problem of neardegene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
514
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 674 publications
(538 citation statements)
references
References 17 publications
4
514
0
5
Order By: Relevance
“…We found that all included local structures contributed significantly to the global network topology across the lifespan. The values and signs of the parameters provide information about the relative contribution of local structures to the overall network topology (Robins et al, 2007a(Robins et al, , 2007b. The negative coefficients for edges and global efficiency (GW NSP ) as well as the positive coefficient for local clustering (GW ESP ) are in line with previous studies using the same approach in functional connectivity datasets (Simpson et al, , 2012.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found that all included local structures contributed significantly to the global network topology across the lifespan. The values and signs of the parameters provide information about the relative contribution of local structures to the overall network topology (Robins et al, 2007a(Robins et al, , 2007b. The negative coefficients for edges and global efficiency (GW NSP ) as well as the positive coefficient for local clustering (GW ESP ) are in line with previous studies using the same approach in functional connectivity datasets (Simpson et al, , 2012.…”
Section: Discussionsupporting
confidence: 82%
“…Their usefulness has been emphasized in social network studies (Robins et al, 2007b), but they may have equal potential for neuronal networks . Until recently, exponential random graph models have been difficult to handle from a statistical point of view, due to the intractability of the normalizing constant and the problem of model degeneracy (Handcock, 2003), which has limited their applicability.…”
Section: Introductionmentioning
confidence: 99%
“…This may be a network dependency at the systemic level rather than strategic action by actors. We thus model reputation using an ERGM with dyadic dependence (Robins et al 2007a(Robins et al , 2007b) and include a model term for cyclical ties and a model term for transitive ties in order to control for the potentially hierarchical nature of the network. These model terms capture the propensity of edges to be involved in cyclical triads (i.e., A → B → C → A) and transitive triads (A → B → C and A → C), respectively.…”
Section: Datasets and Methodologymentioning
confidence: 99%
“…Advances on several fronts have created a sophisticated set of theories and analytical tools that have recently culminated in a 'new science' of networks that spans sociology, physics and organizational sciences (Barabási, 2002;Borgatti et al, 2009;Newman, 2003;Parkhe et al, 2006;Watts, 2004). Statisticians have laid the groundwork for models that allow for inferential hypothesis testing of social theories within a network context as well as longitudinal data analysis to observe and analyse evolution of networks over time (Goodreau, 2007;Handcock, 2003;Krackhardt, 1988;Robins et al, 2007;Snijders, 2002;Snijders et al, 2007).…”
Section: Opportunities and Challenges For Network Research In Public mentioning
confidence: 99%